Can Global De-Carbonization Inhibit Developing Country Industrialization? - Mattoo, Aaditya; Subramanian, Arvind; van der Mensbrugghe, Dominique; He, Jianwu (2012)
Most economic analyses of climate change have focused on the aggregate impact on countries of mitigation actions. The authors depart first in disaggregating the impact by sector, focusing particularly on manufacturing output and exports because of the potential growth consequences. Second, they decompose the impact of an agreement on emissions reductions into three components: the change in the price of carbon due to each country s emission cuts per se; the further change in this price due to emissions tradability; and the changes due to any international transfers (private and public). Manufacturing output and exports in low carbon intensity countries such as Brazil are not adversely affected. In contrast, in high carbon intensity countries, such as China and India, even a modest agreement depresses manufacturing output by 6-7 percent and manufacturing exports by 9-11 percent. The increase in the carbon price induced by emissions tradability hurts manufacturing output most while the Dutch disease effects of transfers hurt exports most. If the growth costs of these structural changes are judged to be substantial, the current policy consensus, which favors emissions tradability (on efficiency grounds) supplemented with financial transfers (on equity grounds), needs re-consideration.